PROCESSO DE PROJETO: UMA REFLEXÃO SOBRE COORDENAÇÃO, COLABORAÇÃO E COMUNICAÇÃO - Duarte, Técia Maria Pereira; Salgado, Monica Santos; Tzortzopoulos, Patricia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The increasing complexity of construction is reflected in the management of the design process. Building design involves a growing number of disciplines, and as such requires increasing levels of coordination and collaboration. As a result, new skills are needed from the professional responsible for design coordination, who must allow the integration of the team, despite different interests and skills, going beyond the simple division of tasks . The social aspect of design development is an extremely important factor because individuals with their abilities, temperaments, psychological characteristics must interact to deliver high quality built environments. Thus, the main purpose of this paper is to discuss the importance of cooperation, collaboration and communication models in design management at architecture undergraduate course. In this sense, a case study has been carried out with final year undergraduate architecture students, to highlight the main difficulties faced by trainee architects. It is observed that the individualism practiced in the classroom can be one of the origins for the difficulties experienced by professionals in developing collaborative and integrated projects.